Liposomes: a promising delivery system for active ingredients in food and nutrition - Noor Akram; Muhammad Afzaal; Farhan Saeed; Yasir Abbas Shah; Zargham Faisal; Aasma Asghar; Huda Ateeq; Gulzar Ahmad Nayik; Sajad H. Wani; Muzzamal Hussain; Mohd Asif Shah; Amin Mousavi Khaneghah (International Journal of Food Properties)
The target delivery of sensitive components to get the intended benefits is a challenge for the global food industry. One of the principal strategies used to boost individualized absorptivity, nutrient stability, and enhanced food quality is the application of liposomal systems in the food industry, which allows controlled release of bioactive compounds. Lipid-oriented encapsulation strategies such as liposomes are superior for encapsulating sensitive components, increasing product solubility and bioavailability, and accurately targeting encapsulated content in food and nutraceutical production. In this review, the nature, composition, and different methodologies for the preparation of liposomes, such as the Bangham Method, ethanol injection method, microfluidic channel method, and freeze-drying method summarized. Moreover, the crucial role of liposomes in delivering sensitive bioactive compounds to cure different health maladies has been emphasized.